2005
DOI: 10.1016/j.taap.2004.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Alteration at translational but not transcriptional level of transferrin receptor expression following manganese exposure at the blood–CSF barrier in vitro

Abstract: Manganese exposure alters iron homeostasis in blood and cerebrospinal fluid (CSF), possibly by acting on iron transport mechanisms localized at the blood-brain barrier and/or blood-CSF barrier. This study was designed to test the hypothesis that manganese exposure may change the binding affinity of iron regulatory proteins (IRPs) to mRNAs encoding transferrin receptor (TfR), thereby influencing iron transport at the blood-CSF barrier. A primary culture of choroidal epithelial cells was adapted to grow on a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 50 publications
5
51
0
Order By: Relevance
“…Research from this laboratory has showed that chronic in vivo exposure to manganese, while reducing blood Fe concentrations, increases iron concentrations in the CSF, suggesting a likely compartment shift of iron from the blood circulation to brain extracellular fluids . Our recent in vitro studies have further demonstrated an increased iron transport at the blood-CSF barrier (Li et al, 2005), a result that may be due to manganese interference on iron regulatory mechanism at the choroid plexus. From the chemistry point of view, manganese ions have many biochemical properties in common with iron including ionic radius, electrical charges in biological matrices, binding affinity for the carrier protein and subcellular accumulation in mitochondria Chen et al, 2001;Zheng et al, 1998).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Research from this laboratory has showed that chronic in vivo exposure to manganese, while reducing blood Fe concentrations, increases iron concentrations in the CSF, suggesting a likely compartment shift of iron from the blood circulation to brain extracellular fluids . Our recent in vitro studies have further demonstrated an increased iron transport at the blood-CSF barrier (Li et al, 2005), a result that may be due to manganese interference on iron regulatory mechanism at the choroid plexus. From the chemistry point of view, manganese ions have many biochemical properties in common with iron including ionic radius, electrical charges in biological matrices, binding affinity for the carrier protein and subcellular accumulation in mitochondria Chen et al, 2001;Zheng et al, 1998).…”
Section: Introductionmentioning
confidence: 76%
“…An increased TfR expression and ensuing elevated iron transport at the BCB may partly explain the disrupted iron status in the CSF (Li et al, 2005). In the current study, we observed that, in addition to action on TfR, manganese exposure increased DMT1 levels in cultured choroidal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The half confluent cultures of Z310, RBE4, N27, or PC12 cells were exposed to 100 µM MnCl 2 containing 2.633 nCi 54 Mn/mL for 24 hrs. The exposure concentration was chosen because previous works by this and other laboratories have shown significant toxic outcomes in various cell types (Chen et al, 2001;Crooks et al, 2007;Li et al, 2005;Zheng and Zhao, 2001). Mn treatment was terminated by rapid aspiration of the medium, followed by thorough washes with 5 mL of ice cold PBS for three times.…”
Section: Mn Exposure and Preparation Of Subcellular Fractionsmentioning
confidence: 99%
“…Previous studies have suggested that Mn 2+ can induce oxidative stress and affect iron metabolism and cellular energy metabolism (Dobson et al, 2004;Erikson et al, 2004a;Hazell, 2002;Li et al, 2005;Lu et al, 2005). Nonetheless, the understanding of the specific mechanisms underlying Mn neurotoxicity in humans remains far from clear.…”
Section: Introductionmentioning
confidence: 99%